Growth response of shallot (Allium ascalonicum L.) varieties on municipal waste compost application - Devi Andriani, Luta; Maimunah , Siregar; Sri Br. PA, Wahyuni (Jurnal Online Pertanian Tropik, 2020)
Growth of shallot plants could be increased through good plant cultivation such as using organic materials that can improve physical, chemical and biological properties in the soil and contain macro and micronutrients so that organic matter is needed in the form of municipal waste compost. The research objective was to study the responsiveness of the growth of onion varieties due to the application of municipal waste compost. This research was carried out in the Bandar Senembah village Binjai district Barat in February-March 2019. The study used a randomized block design (RAK) with 2 factors and 3 blocks. The first factor is the variety (V) and the second factor is Municipal waste compost (K). The results showed that that the best varieties are varieties Bima Brebes. Where the variety showed the highest leaf length per sample and highest number of tillers per sample while the application of municipal waste compost does not show a significant effect on parameters of leaf length per sample but for the number of tillers per sample shows a significant effect where the best results in the application of 3 kg/m2 (plot) municipal waste compost.   REFERENCES   Ahmed, M. E., El-Kader, N. I. A. & Derbala, A.A.E.  (2009). Effect of Irrigation Frequency and Potassium Source on the Productivity, Quality, and Storability of Garlic. Australian Journal Of Basic and Applied Sciences, 3(4), 4490–4497. Alfian, D. F., Nelvia & Yetti, H.  (2015). The Effect of Potassium Fertilizer and Compost Mixture of Oil Palm Empty Bunches with Boiler Ash on Growth and Yield of Onion (Allium ascalonicum L.). Jurnal Agroekoteknologi, 5(2), 1-6. Amiroh, A. (2017). Pengaplikasian dosis pupuk bokashi dan KNO3 terhadap pertumbuhan dan hasil tanaman melon (Cucumis melo L.). Jurnal Saintis, 9(1), 25 - 36. Arisha, H. M. E.,. Ibraheim, S. K. A & El-Sarkassy, N. M. (2017). The response of garlic (Allium sativum L.) yield, volatile oil, and nitrate content to foliar and soil application of potassium fertilizer under sandy soil conditions. Middle East Journal of Applied Sciences, 7(1), 44-56. Aslamiah, I. D., dan Sularno. (2017). The response of growth and production of peanut plants of the addition of organic fertilizer concentration and reduction of an organic fertilizer dosage. Prosiding Seminas Nasional Fakultas Pertanian UMJ. BPS. (2018). Statistik Indonesia. Badan Pusat Statistik Republik Indonesia, Jakarta. Gunadi, N. (2009). Kalium sulfat dan kalium klorida sebagai sumber pupuk kalium pada tanaman bawang merah. Jurnal Hortikultura, 19(2),174-185. Hickey, M. (2012). Growing Garlic in NSW Second Edition. Primefact 259. Department of Primary Industries. NSW Government. Australia. Hilal, M.H., Selim, A.M. & El-Neklawy, A.S.  (1992). Enhancing and retarding effect of combined sulfur and fertilizer applications on crop production in different soils. In Proceedings Middle East Sulphur Symposium 12-16 February, Cairo, Egypt. Marschner, P.( 2012). Mineral Nutrition of Higher Plants Third Edition. Elsevier Ltd. Oxford. Nainwal, R. C., Sigh, D., Katiyar, R. S., Sharma, I & Tewari, S. K. (2015). The response of garlic to integrated nutrient management practices in a sodic soil of Uttar Pradesh, India. Journal of Spices and Aromatic Crops, 24(1), 33-36. Putra, A. A. G. (2013). Kajian aplikasi dosis pupuk ZA dan kalium  pada tanaman bawang putih (Allium sativum  L.). Jurnal Ganec Swara, 7(2), 10–18. Setiawati, W., Murtiningsih, R., Sopha, G. A & Handayani, T. (2007). Petunjuk Teknis Budidaya Tanaman Sayuran. Balai Penelitian Tanaman Sayuran. Shafeek, M. R., Nagwa, M. H., Singer, S. M., & El-Greadly, N. H. (2013). Effect of potassium fertilizer and foliar spraying with Ethereal on plant development, yield, and bulb quality of onion plants (Allium cepa L). Journal of Applied Sciences Research, 9(2), 1140-1146. Sholihin, Y., Suminar, E., Rizky, W.H. & Pitaloka, G.G. (2016). Meristem explants growth of garlic (Allium sativum L.) Cv. tawangmangu on various compositions of kinetin and ga3 in vitro. Jurnal Kultivasi, 15(3), 172–179. Sulichantini, E. D. (2016). Effect of plant growth regulator Concentration Against Regeneration Garlic (Allium sativum L) In the Tissue Culture.. Jurnal Agrifor, 15(1), 29–38. Suminarti, N.E. (2010). The Effects of N and K Fertilization on the Growth and Yield of Taro on Dry Land. Akta Agrosia, 13(1), 1–7. Uke, K. H. Y., Barus, H & Madauna, I. W.  (2015). Effect of Tuber Sizes and Potassium Dosages on Growth and Production of Shallots var. Lembah Palu. Jurnal Agrotekbis, 3(6), 655 - 661. Utomo, P.S & Suprianto, A. (2019). Respon pertumbuhan dan produksi tanaman bawang merah (Allium ascalonicum L.) varietas thailand terhadap perlakuan dosis pupuk kusuma bioplus dan KNO3 putih. Jurnal Ilmiah Hijau Cendekia, 4(1), 28–34. Wu, C., Wang, M., Cheng, Z & Meng, H. (2016). The response of garlic (Allium sativum L.) bolting and bulbing to temperature and photoperiod treatments. Biol Open,  5(4), 507-518.